Estudo sobre apropriação cultural científica numa perspectiva afrocêntrica em aulas de química - Lima, Michel Marques de (2022)
This study is based on the afrocentric perspective and has as it’s general objective to investigate how it is possible to use afrocentricity as a tool in the construction of an afrocentric proposal for the chemistry teaching that is in line with the demands of Law 10.639/03 and related documents. We captured the data using filmic resources and transcribed the audios dividing them into turns. The extracts analyzes were divided according to the technique of Conversation Analysis and discussed using the afrocentric lens. The results show possibilities of apprehending chemical concepts in afrocentric classes and that it is possible to build counter-hegemonic pedagogical resources in chemistry teaching, and these can come to meet the political demands of black population.